Visual guide to financial markets - Wilson, David, 1958 March 28- (Hoboken, N.J. : Wiley, 2012)
A highly visual look at major investment opportunities from the minds at BloombergThe essential guide for anyone trying to get a handle on the fundamentals of investing, the Bloomberg Visual Guide to Financial Markets distills 30 years of Bloomberg expertise into one straightforward, easy-to-read volume. The book teaches readers about three basic investment options & amp;mdash;governments, companies, and real assets, including gold and other commodities & amp;mdash;and offers valuable insights into money-market securities, bonds, stocks, derivatives, mutual funds, exchange-traded funds, and alternatives. D.
Overview -- Government -- Companies -- Hard assets -- Indexes -- Government revisited -- Companies revisited -- Hard assets revisited -- Overview -- Derivatives -- Mutual funds and exchange-traded funds -- Indexes revisited.
Includes bibliographical references and index.
Print version record.
Keywords: Finance; Capital market; Investments; Finance; Capital market; Investments; Capital market; Finance; Investments; Finance; Capital market; Investments; Electronic books